Fischer-Tropsch synthesis: Direct cobalt nitrate reduction of promoted Co/TiO2 catalysts. (1st June 2019) - Mehrbod, Mohammad; Martinelli, Michela; Martino, Annabelle G.; Cronauer, Donald C.; Jeremy Kropf, A.; Marshall, Christopher L.; Jacobs, Gary
Graphical abstract: Highlights: H2 activated air calcined PtCo/TiO2 catalyst had larger, more reducible Co 0 clusters. The Co clusters sintered in Fischer-Tropsch synthesis: lower steady state conversion, lower stability. Direct cobalt nitrate reduction of PtCo/TiO2 resulted in smaller, more interacting Co 0 clusters. The Co clusters from direct nitrate reduction exhibited higher steady state conversion and stability. Abstract: The effect of the direct reduction of cobalt nitrate versus the more conventional calcination/reduction treatment has been investigated. Porosity properties of the catalysts are not significantly modified by avoiding the calcination step, as similar BET surface area, pore volume and pore diameter are obtained for the activated catalysts. In contrast, the cobalt reducibility decreases, but smaller cobalt particles size and higher dispersion are obtained. The reduction phenomena occurring for the uncalcined catalysts are more complex because of the additional nitrate decomposition steps. TPR-MS and TPR-XANES point out that CoOx intermediate species are formed during the reductive nitrate decomposition. However, these species are oxidized by NOX (formed by nitrate decomposition) to spinel type Co3 O4, which is then converted to CoO prior to the final reduction step to Co 0 . The addition of promoters (Pt, Re, Ru, Ag) improves the cobalt reducibility, especially by shifting the final reduction step (i.e., CoO to Co 0 ) to lower temperature. FT activity testing data show that activated uncalcined catalysts have higher CO conversion following the initial decline and leveling off period relative to the activated calcined catalyst. The best performance is achieved with uncalcined Pt-12%Co/TiO2 . This catalyst has the highest CO steady state conversion, which is 1.2 times higher than the Pt-promoted calcined catalyst. Moreover, its deactivation rate is 0.13%/h compared to 0.2%/h for the corresponding calcined catalyst. The difference in the catalytic activity is even higher for the un-promoted samples, where the activated uncalcined catalyst has almost double the CO conversion as compared to its calcined counterpart. Finally, the addition of other promoters such as Ru, Re and Ag has no significant effect on catalytic activity.